(3GdnqJrbpQjH hGdJjSjQ derYpQnaI Snff GdHTjQ GdfPjQs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQqj GdcQOj GdTQNGfj, CHh YeQh, Jbqj GdOjf, GdeYQha HGHf GdUdGM, (B643 (3g` s ((3CMeO GdMSjf HTGQg s)
(3ChdgG (B:s
(3bGd GdTjN Gdfhhj CeG HYO aEf Yde GdMOjK ef CaVd GdobQH Edi QH GdYGdejf hcja dGjchf hgPG cJGH GNJUQJg ef cJGH GdEQTGO GdPj GNJUQJg ef Ydhe GdMOjK ddTjN GdEeGeGHf GdUdGM s
(3BNQgG (B:s
(3ojMJed Cf jchf GdeQGO HgG gPG GdEQTGO hojMJed Cf ojQGO HgG gh GdJbQjH aj GdJaSjQ GfJgi s
(3GdfSNI HgG MhGTs
(3efbhdg ef fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUWdM Mdje (B3) s
Keywords: (3GdMOjK h GdeUWdMs